Membrane electrode catalyst layer with gradient aperture structure and manufacturing method thereof

By designing a gradient pore size structure in the membrane electrode catalytic layer, the problem of "water flooding" in the membrane electrode catalytic layer is solved, the gas and reactants transmission performance of the battery is improved, and the performance and stability of the fuel cell are improved.

CN119852457AActive Publication Date: 2025-04-18SHENZHEN ACAD OF AEROSPACE TECH

Patent Information

Application Number
CN202411865849.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-04-18
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

The existing membrane electrode catalytic layer is prone to 'water flooding' during use, resulting in the gas transmission channel being blocked and affecting battery performance.

Method used

A membrane electrode catalytic layer with a gradient pore size structure is designed, and is bonded to the side of the proton exchange membrane by hot pressing. The catalytic layer includes three catalytic sub-layers. The mass ratio of the catalyst and the foaming agent of each layer is gradually reduced to form a gradually increasing pore size and porosity.

Benefits of technology

It effectively reduces the probability of "water flooding" in the gas diffusion layer, improves the transmission performance of battery gas and reactants, and thus improves the maximum power and stability of the fuel cell.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of membrane electrodes, in particular to a membrane electrode catalyst layer with a gradient aperture structure and a manufacturing method thereof.The catalyst layer is attached to the side face of a proton exchange membrane through hot pressing, and the catalyst layer at least comprises three catalyst sub-layers; the catalytic sublayer comprises ultrapure water, an organic solvent, a catalyst, a foaming agent and an ionomer; in the direction far away from the proton exchange membrane, the mass ratio of the catalyst to the foaming agent in different catalytic sub-layers is gradually reduced, and the pore diameter and the porosity in the catalytic layers are gradually increased. The membrane electrode catalyst layer provided by the embodiment of the invention can reduce the probability of'flooding 'of the gas diffusion layer (GDL) and improve the transmission performance of battery gas and reactants.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of membrane electrode technology, and in particular to a membrane electrode catalyst layer with a gradient pore size structure and a manufacturing method thereof. Background Art

[0002] Membrane Electrode Assembly (MEA) is the core component of Proton Exchange Membrane Fuel Cell (PEMFC). It provides microchannels and electrochemical reaction sites for multiphase material transfer for PEMFC. The membrane electrode consists of three parts: proton exchange membrane (PEM), catalyst layer (CL) and gas diffusion layer (GDL). It undertakes the important task of promoting the chemical reaction between hydrogen and oxygen to generate electricity. During the operation of the membrane electrode, the catalyst layer is the main place for hydrogen and oxygen to react. This reaction area not only involves the transfer of electrons and protons, but also includes the transfer of heat and gas and the migration of water. Therefore, the design quality of the catalyst layer determines the performance of the fuel cell to a large extent. Since the reaction rate of the anode in the fuel cell is usually several times that of the cathode, the electrical performance of the battery is mainly affected by the design of the cathode catalyst layer.

[0003] In order to improve the power performance of fuel cells, the improvement methods of fuel cell catalyst layers are mainly reflected in two aspects: on the one hand, by improving the performance of materials such as catalysts, carbon paper, and bipolar plates, the performance and life of fuel cells are improved, and the manufacturing cost is reduced; on the other hand, with the development of manufacturing processes, the performance and life of fuel cells are improved, and the manufacturing cost is also reduced. So far, the manufacturing technology of the catalyst layer has evolved from the gas diffusion electrode (Gas Diffusion Electrode, GDE) process to the catalyst coated proton membrane (CCM). At present, the mainstream manufacturing technology of the catalyst layer has turned to gradient design. This gradient design not only improves the power performance of MEA, but also reduces the amount of platinum (Pt) in the catalyst layer, meeting the operation requirements of fuel cells under low humidity, high current density and low platinum loading conditions. However, the probability of "flooding" of the gas diffusion layer (GDL) in the prior art is still very high. When excessive water accumulates in the GDL, it will block the gas transmission channel, affect the transmission of gas and reactants, and thus reduce the performance of the battery. Summary of the invention

[0004] In order to solve the problems in the above-mentioned background technology, the first object of the present invention is to provide a membrane electrode catalyst layer with a gradient pore size structure, which can reduce the probability of "flooding" of the gas diffusion layer (GDL) and improve the transmission performance of battery gases and reactants.

[0005] The solution adopted by the present invention to solve the technical problem is: a membrane electrode catalyst layer with a gradient pore size structure, the catalyst layer is attached to the side of the proton exchange membrane by hot pressing, and the catalyst layer includes at least three catalyst sub-layers;

[0006] The constituent materials of the catalyst sublayer include ultrapure water, organic solvent, catalyst, foaming agent and ionomer; in the direction away from the proton exchange membrane, the mass ratio of catalyst to foaming agent in different catalyst sublayers gradually decreases, and the pore size and porosity in the catalyst layer gradually increase.

[0007] Furthermore, the catalytic layer includes a first catalytic sublayer, a second catalytic sublayer and a third catalytic sublayer; the first catalytic sublayer is formed by applying a first slurry to the surface of a proton exchange membrane and then drying it, and the first slurry includes ultrapure water, an organic solvent, a catalyst, a foaming agent and an ionomer; the content of the catalyst in the first slurry is 1wt% to 50wt%, the content of the organic solvent is 1wt% to 80wt%, the content of the ultrapure water is 10wt% to 90wt%, the content of the foaming agent is 1wt% to 10wt%, and the content of the ionomer is 0.8 to 2 times the content of the catalyst;

[0008] The second catalyst sublayer is formed by applying a second slurry to a side of the first catalyst sublayer away from the proton exchange membrane and then drying, wherein the second slurry comprises ultrapure water, an organic solvent, a catalyst, a foaming agent, an ionomer and a hydrophobic agent; the content of the catalyst in the second slurry is 1wt% to 50wt%, the content of the organic solvent is 1wt% to 80wt%, the content of the ultrapure water is 10wt% to 90wt%, the content of the ionomer is 0.8 to 2 times the content of the catalyst, the content of the foaming agent is 1wt% to 10wt%, and the content of the hydrophobic agent is 1wt% to 30wt%; the content of the catalyst in the second slurry is lower than the content of the catalyst in the first slurry; the content of the ionomer in the second slurry is lower than the content of the ionomer in the first slurry;

[0009] The third catalyst sublayer is formed by applying a third slurry to a side of the second catalyst sublayer away from the first catalyst sublayer and then drying it, wherein the third slurry includes ultrapure water, an organic solvent, a catalyst, a foaming agent, an ionomer and a hydrophobic agent; the content of the catalyst in the third slurry is 1wt% to 50wt%, the content of the organic solvent is 1wt% to 80wt%, the content of the ultrapure water is 10wt% to 90wt%, the content of the foaming agent is 1wt to 10wt%, and the content of the hydrophobic agent is 1wt to 30wt%; the content of the catalyst in the third slurry is lower than the content of the catalyst in the second slurry; the content of the ionomer in the third slurry is lower than the content of the ionomer in the second slurry; the content of the hydrophobic agent in the third slurry is higher than the content of the hydrophobic agent in the second slurry.

[0010] Furthermore, the mass ratio of the catalyst, ultrapure water and organic solvent in the first slurry is 1:7:3; the mass ratio of the catalyst to the blowing agent and the ionomer is 1:2:(2-6.9); the mass ratio of the catalyst, ultrapure water and organic solvent in the second slurry is 1:7:3; the mass ratio of the catalyst to the blowing agent, the ionomer and the hydrophobic agent is 1:(2-3):6.9:0.05; the catalyst in the third slurry is carbon powder, and the mass ratio of the catalyst, ultrapure water and organic solvent in the third slurry is 1:6:3; the mass ratio of the catalyst to the blowing agent, the ionomer and the hydrophobic agent is 1:5:3.45:0.08.

[0011] Furthermore, the catalyst on the first slurry and the second slurry is one or a mixture of any of Pt / C, PtRu, PtRu / C, PtFe / C, PtCo / C, PtNi / C, PtAu / C, PtPd / C, PtPb / C, and PtMn / C, and the Pt loading in the catalyst is 30wt%-70wt%.

[0012] Furthermore, the hydrophobic agent is one of polyvinylidene fluoride (PVDF) or polytetrafluoroethylene (PTFE) or any combination of the two.

[0013] Furthermore, the foaming agent is one or any combination of polystyrene, DNTA, NTA, and ammonium bicarbonate.

[0014] Furthermore, the ionomer is one or any combination of D2020, D520, and D79-25BS.

[0015] Optionally, the organic solvent in the present application may be one or any combination of ethanol, isopropanol, n-propanol, n-butanol, etc.

[0016] The second object of the present invention is to provide a method for preparing a membrane electrode catalyst layer with a simple process, comprising the following steps:

[0017] S1, preparing the first slurry

[0018] Weigh the catalyst, ultrapure water and organic solvent respectively, add ultrapure water to the catalyst, shake well and then add the organic solvent, then shear and disperse for 20 minutes with a shearing machine to obtain a dispersion; add the ionomer solution and the foaming agent to the dispersion, then shear and disperse for another 20 minutes to obtain a first slurry;

[0019] S2, preparing the second slurry

[0020] Weigh the catalyst, ultrapure water and organic solvent respectively, add ultrapure water to the catalyst, shake well and then add the organic solvent, then shear and disperse for 20 minutes with a shearing machine to obtain a dispersion; add an ionomer solution, a foaming agent and a hydrophobic agent to the dispersion, then shear and disperse for another 20 minutes to obtain a second slurry;

[0021] S3, preparing the third slurry

[0022] Weigh the catalyst, ultrapure water and organic solvent respectively, add ultrapure water to the catalyst, shake well and then add the organic solvent, then shear and disperse for 20 minutes with a shearing machine to obtain a dispersion; add the ionomer solution, foaming agent and hydrophobic agent to the dispersion, then shear and disperse for another 20 minutes to obtain a third slurry;

[0023] S4, Preparation of Gradient Pore Structure Membrane Electrode

[0024] The first slurry, the second slurry and the third slurry are sequentially applied to both sides of the proton exchange membrane by slit coating, and then the proton exchange membrane is placed in a dry air atmosphere for foaming until the foaming is complete, thereby forming a cathode catalyst layer and an anode catalyst layer with a gradient pore structure, wherein the cathode catalyst layer includes a cathode first catalytic sublayer, a cathode second catalytic sublayer and a cathode third catalytic sublayer, and the anode catalyst layer includes an anode first catalytic sublayer, anode second catalytic sublayer and anode third catalytic sublayer.

[0025] Furthermore, in the step S4, the foaming temperature is 30-100° C., and the foaming time is 10 min-24 h.

[0026] In summary, the beneficial effects of the present invention are as follows: through the different foaming speeds of slurries with different foaming agent concentrations and the temperature gradient transmission effect on catalyst sublayers at different levels when heated, a gradient-distributed pore structure is formed in the catalyst layer, thereby reducing the probability of "flooding" of the gas diffusion layer and improving the transmission performance of battery gas and reactants;

[0027] At the same time, the concentration of the catalyst and polytetrafluoroethylene is adjusted to form a gradient catalytic layer structure and a hydrophilic-hydrophobic structure, achieving an ordered hydrophilic-hydrophobic structure and a gradual pore distribution, thereby improving the maximum power and stability of the proton exchange membrane fuel cell (PEMFC), thereby making a high-efficiency, low-cost and long-life PEMFC.

[0028] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present invention more obvious and easy to understand, the following preferred embodiments are specifically cited and described in detail as follows. DETAILED DESCRIPTION

[0029] In order to make the content of the present invention more clearly understood, the present invention is further described below based on specific embodiments.

[0030] The D520-Naf ion ionomer solution in the following examples is a Nafion solution with a mass concentration of 5%.

[0031] Embodiment 1

[0032] S1, preparing the first slurry

[0033] 1 g of Pt / C, 7 g of ultrapure water and 3 g of isopropanol were weighed respectively, wherein the platinum content in Pt / C was 50 wt %, ultrapure water was added to Pt / C, and isopropanol was added after shaking, followed by shearing and dispersion for 20 min using a shearing machine to obtain a dispersion; 6.9 g of D520-Nafion ionomer solution and 2 g of ammonium bicarbonate were added to the dispersion, and then sheared and dispersed for another 20 min to obtain a first slurry.

[0034] S2, preparing the second slurry

[0035] 1 g of Pt / C, 7 g of ultrapure water and 3 g of isopropanol were weighed respectively, wherein the platinum content in Pt / C was 50 wt %, ultrapure water was added to Pt / C, and isopropanol was added after shaking, followed by shearing and dispersion for 20 min using a shearing machine to obtain a dispersion; 6.9 g of D520-Naf ion ionomer solution, 3 g of polystyrene and 0.05 g of 20% PTFE emulsion were added to the dispersion, followed by shearing and dispersion for 20 min to obtain a second slurry.

[0036] S3, preparing the third slurry

[0037] Weigh 2g VC-72R superconducting carbon powder, 12g ultrapure water and 6g isopropanol respectively, add ultrapure water to the VC-72R superconducting carbon powder, shake well and then add isopropanol, then shear and disperse for 20 minutes with a shearing machine to obtain a dispersion; add 3.45g D520-Naf ion ionomer solution, 5g polystyrene and 0.08g PTFE emulsion with a concentration of 20% to the dispersion, then shear and disperse for 20 minutes to obtain a third slurry.

[0038] S4, Preparation of Gradient Pore Structure Membrane Electrode

[0039] The first slurry, the second slurry and the third slurry are sequentially applied to both sides of the proton exchange membrane by slit coating to achieve a target Pt loading or carbon loading of 0.3 mg Pt / cm 2 、0.1mgPt / cm 2 and 0.3mgC / cm 2 The proton exchange membrane is then placed in a dry air atmosphere at 95°C for foaming for 6 hours. After the foaming is complete, a cathode catalyst layer and an anode catalyst layer with a gradient pore structure are formed, wherein the cathode catalyst layer includes a first cathode catalyst sublayer, a second cathode catalyst sublayer, and a third cathode catalyst sublayer, and the anode catalyst layer includes a first anode catalyst sublayer, a second anode catalyst sublayer, and a third anode catalyst sublayer.

[0040] Embodiment 2

[0041] S1, preparing the first slurry

[0042] 1 g of PtCo / C, 7 g of ultrapure water and 3 g of isopropanol were weighed respectively, wherein the platinum content in PtCo / C was 25 wt %, ultrapure water was added to PtCo / C, and isopropanol was added after shaking, followed by shearing and dispersion for 20 minutes using a shearing machine to obtain a dispersion; 2 g of D520-Naf ion ionomer solution and a foaming agent, wherein the foaming agent was a mixture of 2 g of ammonium bicarbonate and 1 g of DNTA, were added to the dispersion, and then shearing and dispersion was performed for 20 minutes to obtain a first slurry.

[0043] S2, preparing the second slurry

[0044] 1 g of Pt / C, 7 g of ultrapure water and 3 g of isopropanol were weighed respectively, wherein the platinum content in Pt / C was 50 wt %, ultrapure water was added to Pt / C, and isopropanol was added after shaking, followed by shearing and dispersion for 20 min using a shearing machine to obtain a dispersion; 6.9 g of D520-Naf ion ionomer solution, 3 g of polystyrene and 0.05 g of 20% PTFE emulsion were added to the dispersion, followed by shearing and dispersion for 20 min to obtain a second slurry.

[0045] S3, preparing the third slurry

[0046] Weigh 2g VC-72R superconducting carbon powder, 12g ultrapure water and 6g isopropanol respectively, add ultrapure water to the VC-72R superconducting carbon powder, shake well and then add isopropanol, then shear and disperse for 20 minutes with a shearing machine to obtain a dispersion; add 3.45g D520-Naf ion ionomer solution, 5g polystyrene and 0.08g PTFE emulsion with a concentration of 20% to the dispersion, then shear and disperse for 20 minutes to obtain a third slurry.

[0047] S4, Preparation of Gradient Pore Structure Membrane Electrode

[0048] The first slurry, the second slurry and the third slurry are sequentially applied to both sides of the proton exchange membrane by slit coating to achieve a target Pt loading or carbon loading of 0.2 mg Pt / cm 2 、0.05mgPt / cm 2 and 0.2mgC / cm 2 The proton exchange membrane is then placed in a dry air atmosphere at 95°C for foaming for 6 hours. After the foaming is complete, a cathode catalyst layer and an anode catalyst layer with a gradient pore structure are formed, wherein the cathode catalyst layer includes a first cathode catalyst sublayer, a second cathode catalyst sublayer, and a third cathode catalyst sublayer, and the anode catalyst layer includes a first anode catalyst sublayer, a second anode catalyst sublayer, and a third anode catalyst sublayer.

[0049] Embodiment 3

[0050] S1, preparing the first slurry

[0051] 1 g of Pt / C, 7 g of ultrapure water and 3 g of isopropanol were weighed respectively, wherein the platinum content in Pt / C was 50 wt %, ultrapure water was added to Pt / C, and isopropanol was added after shaking, followed by shearing and dispersion for 20 minutes using a shearing machine to obtain a dispersion; 6.9 g of D520-Nafion ionomer solution and 2 g of ammonium bicarbonate were added to the dispersion, and then shearing and dispersion for another 20 minutes were performed to obtain a first slurry.

[0052] S2, preparing the second slurry

[0053] 1 g of Pt / C, 0.01 g of IrO2, 7 g of ultrapure water and 3 g of isopropanol were weighed respectively, wherein the platinum content in Pt / C was 50 wt %, Pt / C and IrO2 were mixed together to form a catalyst mixture, ultrapure water was added to the catalyst mixture, and isopropanol was added after shaking, followed by shearing and dispersion for 20 min using a shearing machine to obtain a dispersion; 6.9 g of D520-Nafion ionomer solution, 2 g of polystyrene and 0.05 g of 20% PTFE emulsion were added to the dispersion, and then sheared and dispersed for another 20 min to obtain a second slurry.

[0054] S3, preparing the third slurry

[0055] Weigh 2g VC-72R superconducting carbon powder, 12g ultrapure water and 6g isopropanol respectively, add ultrapure water to the VC-72R superconducting carbon powder, shake well and then add isopropanol, then shear and disperse with a shearing machine for 20 minutes to obtain a dispersion; add 3.45g D520-Nafion ionomer solution, 5g polystyrene and 0.08g PTFE emulsion with a concentration of 20% to the dispersion, then shear and disperse for another 20 minutes to obtain a third slurry.

[0056] S4, Preparation of Gradient Pore Structure Membrane Electrode

[0057] The first slurry, the second slurry and the third slurry are sequentially applied to both sides of the proton exchange membrane by slit coating to achieve a target Pt loading or carbon loading of 0.25 mg Pt / cm 2 、0.1mgPt / cm 2 and 0.2mgC / cm 2 The proton exchange membrane is then placed in a dry air atmosphere at 95°C for foaming for 6 hours. After the foaming is complete, a cathode catalyst layer and an anode catalyst layer with a gradient pore structure are formed, wherein the cathode catalyst layer includes a first cathode catalyst sublayer, a second cathode catalyst sublayer, and a third cathode catalyst sublayer, and the anode catalyst layer includes a first anode catalyst sublayer, a second anode catalyst sublayer, and a third anode catalyst sublayer.

[0058] The embodiments described above are only preferred implementation modes of the present invention and cannot be used to limit the protection scope of the present invention. Any non-substantial changes and modifications made by those skilled in the art on the basis of the invention shall fall within the protection scope of the present invention.

Claims

1. A membrane electrode catalyst layer having a gradient pore size structure, characterized in that: The catalyst layer is attached to the side of the proton exchange membrane by hot pressing, and the catalyst layer comprises at least three catalyst sub-layers; The constituent materials of the catalyst sublayer include ultrapure water, organic solvent, catalyst, foaming agent and ionomer; in the direction away from the proton exchange membrane, the mass ratio of catalyst to foaming agent in different catalyst sublayers gradually decreases, and the pore size and porosity in the catalyst layer gradually increase.

2. The membrane electrode catalyst layer with a gradient pore size structure according to claim 1, characterized in that: The catalytic layer includes a first catalytic sublayer, a second catalytic sublayer and a third catalytic sublayer; The first catalyst sublayer is formed by coating a first slurry on the surface of a proton exchange membrane and then drying it, wherein the first slurry includes ultrapure water, an organic solvent, a catalyst, a foaming agent and an ionomer; the content of the catalyst in the first slurry is 1wt% to 50wt%, the content of the organic solvent is 1wt% to 80wt%, the content of the ultrapure water is 10wt% to 90wt%, the content of the foaming agent is 1wt% to 10wt%, and the content of the ionomer is 0.8 to 2 times the content of the catalyst; The second catalyst sublayer is formed by applying a second slurry to a side of the first catalyst sublayer away from the proton exchange membrane and then drying, wherein the second slurry comprises ultrapure water, an organic solvent, a catalyst, a foaming agent, an ionomer and a hydrophobic agent; the content of the catalyst in the second slurry is 1wt% to 50wt%, the content of the organic solvent is 1wt% to 80wt%, the content of the ultrapure water is 10wt% to 90wt%, the content of the ionomer is 0.8 to 2 times the content of the catalyst, the content of the foaming agent is 1wt% to 10wt%, and the content of the hydrophobic agent is 1wt% to 30wt%; the content of the catalyst in the second slurry is lower than the content of the catalyst in the first slurry; the content of the ionomer in the second slurry is lower than the content of the ionomer in the first slurry; The third catalyst sublayer is formed by applying a third slurry to a side of the second catalyst sublayer away from the first catalyst sublayer and then drying it, wherein the third slurry includes ultrapure water, an organic solvent, a catalyst, a foaming agent, an ionomer and a hydrophobic agent; the content of the catalyst in the third slurry is 1wt% to 50wt%, the content of the organic solvent is 1wt% to 80wt%, the content of the ultrapure water is 10wt% to 90wt%, the content of the foaming agent is 1wt to 10wt%, and the content of the hydrophobic agent is 1wt to 30wt%; the content of the catalyst in the third slurry is lower than the content of the catalyst in the second slurry; the content of the ionomer in the third slurry is lower than the content of the ionomer in the second slurry; the content of the hydrophobic agent in the third slurry is higher than the content of the hydrophobic agent in the second slurry.

3. The membrane electrode catalyst layer with a gradient pore size structure according to claim 2, characterized in that: The mass ratio of the catalyst, ultrapure water and organic solvent in the first slurry is 1:7:3; the mass ratio of the catalyst, the blowing agent and the ionomer is 1:2:(2-6.9); The mass ratio of the catalyst, ultrapure water and organic solvent in the second slurry is 1:7:3; the mass ratio of the catalyst to the foaming agent, ionomer and hydrophobic agent is 1:(2-3):6.9:0.05; The catalyst in the third slurry is carbon powder, and the mass ratio of the catalyst, ultrapure water and organic solvent in the third slurry is 1:6:3; the mass ratio of the catalyst to the foaming agent, ionomer and hydrophobic agent is 1:5:3.45:0.

08.

4. The membrane electrode catalyst layer with a gradient pore size structure according to claim 2, characterized in that: The catalyst on the first slurry and the second slurry is one or a mixture of any of Pt / C, PtRu, PtRu / C, PtFe / C, PtCo / C, PtNi / C, PtAu / C, PtPd / C, PtPb / C, and PtMn / C, and the Pt loading in the catalyst is 30wt%-70wt%.

5. The membrane electrode catalyst layer with a gradient pore size structure according to claim 2, characterized in that: The hydrophobic agent is one of polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE) or any combination of the two.

6. The membrane electrode catalyst layer with a gradient pore size structure according to claim 2, characterized in that: The foaming agent is one or any combination of polystyrene, DNTA, NTA and ammonium bicarbonate.

7. The membrane electrode catalyst layer with a gradient pore size structure according to claim 2, characterized in that: The ionomer is one of D2020, D520, and D79-25BS, or any combination thereof.

8. A method for preparing a membrane electrode catalyst layer according to any one of claims 2 to 8, characterized in that: The following steps are involved: S1, preparing the first slurry Weigh the catalyst, ultrapure water and organic solvent respectively, add ultrapure water to the catalyst, shake well and then add the organic solvent, then shear and disperse for 20 minutes with a shearing machine to obtain a dispersion; add the ionomer solution and the foaming agent to the dispersion, then shear and disperse for another 20 minutes to obtain a first slurry; S2, preparing the second slurry Weigh the catalyst, ultrapure water and organic solvent respectively, add ultrapure water to the catalyst, shake well and then add the organic solvent, then shear and disperse for 20 minutes with a shearing machine to obtain a dispersion; add an ionomer solution, a foaming agent and a hydrophobic agent to the dispersion, then shear and disperse for another 20 minutes to obtain a second slurry; S3, preparing the third slurry Weigh the catalyst, ultrapure water and organic solvent respectively, add ultrapure water to the catalyst, shake well and then add the organic solvent, then shear and disperse for 20 minutes with a shearing machine to obtain a dispersion; add the ionomer solution, foaming agent and hydrophobic agent to the dispersion, then shear and disperse for another 20 minutes to obtain a third slurry; S4, Preparation of Gradient Pore Structure Membrane Electrode The first slurry, the second slurry and the third slurry are sequentially applied to both sides of the proton exchange membrane by slit coating, and then the proton exchange membrane is placed in a dry air atmosphere for foaming until the foaming is complete, thereby forming a cathode catalyst layer and an anode catalyst layer with a gradient pore structure, wherein the cathode catalyst layer includes a cathode first catalytic sublayer, a cathode second catalytic sublayer and a cathode third catalytic sublayer, and the anode catalyst layer includes an anode first catalytic sublayer, anode second catalytic sublayer and anode third catalytic sublayer.

9. The preparation method according to claim 8, characterized in that: In the step S4, the foaming temperature is 30-100° C., and the foaming time is 10 min-24 h.

Citation Information

Patent Citations

  • Cathode catalytic membrane, membrane electrode, preparation method of membrane electrode and fuel cell

    CN115000420A

  • Cathode catalytic membrane and preparation method thereof, membrane electrode and fuel cell

    CN115188971A

  • Fuel cell membrane electrode with gradient structure and preparation method thereof

    CN116364947A

  • Aperture gradient cathode catalyst layer and preparation method and application thereof

    CN116364948A

Cited By

  • Gradient porous three-dimensional interpenetrating network direct ammonia fuel cell membrane electrode

    CN120933409A

  • A gradient porous three-dimensional interpenetrating network direct ammonia fuel cell membrane electrode

    CN120933409B